Kasifikasi Kondisi Saluran Drainase Perkotaan Berdasarkan Dimensi, Ketinggian Air, Dan Sedimentasi Di Medan, Indonesia - Fifi Aliyda; Zulham Prasetyo; Yuni Yolanda; Rizky Simanjuntak; Rumillah Harahap; Wisnu Prayogo (CV. SINAR HOWUHOWU, 2026)
Urban drainage systems play an important role in managing stormwater runoff in urban areas. Rapid urban development often reduces infiltration areas and increases surface runoff, which can lead to flooding and waterlogging in several locations. This study aims to analyze the performance of urban drainage systems and identify factors causing water inundation in urban areas. The research method used is a descriptive quantitative approach by evaluating drainage channels based on rainfall data, channel capacity, sedimentation conditions, and supporting environmental factors. Secondary data were collected from previous studies and hydrological analysis results. The analysis includes rainfall intensity calculation, runoff discharge estimation, and comparison with existing drainage channel capacity. The results show that several drainage channels are unable to accommodate the design discharge due to sedimentation, waste accumulation, and changes in land use. In addition, insufficient maintenance of drainage channels also contributes to the reduced performance of the drainage system. Therefore, improvements in drainage channel capacity, routine maintenance, and integrated urban drainage planning are needed to reduce flood risks in urban areas. The results of this study are expected to provide useful information for local governments in improving urban drainage management systems.